Navigating Challenges: Mental Health as a Mediator in the Performance of Indonesian Seafarers - Sudewo, Gatot Cahyo; Jinca, Muhammad Yamin; Sukardiman, Tjuk; Octora, Theresye Yoanita (Media Ekonomi dan Manajemen, 2024)
The mental health and overall quality of seafarers are critical to the safety and efficiency of maritime operations. This study investigates the factors influencing the quality of Indonesian seafarers, with a particular focus on mental health as a mediating variable. Using Structural Equation Modeling (SEM) with Partial Least Squares (PLS), we analyzed data from 280 respondents, including skippers and crew members working on Indonesian flagged ships. The study examines the impact of working conditions, recruitment and placement, training and development, and safety culture on seafarer quality, both directly and indirectly through mental health. Our findings indicate that mental health significantly mediates the relationship between these factors and the quality of seafarers. Training and development emerged as the most influential factor, followed by safety culture, recruitment and placement, and working conditions. The results emphasize the importance of enhancing mental health support to improve working conditions, recruitment processes, training initiatives, and safety culture, thereby increasing productivity and the overall quality of seafarers. This research addresses an empirical gap by providing practical strategies to improve Indonesian seafarers' quality and job stability in the global maritime industry. Future research should expand the geographic scope and explore additional factors affecting seafarer quality and mental health.